Probiotic Microcapsul of Lactobacillus rhamnosus FBB81 and Its Viability During Storage - Nocianitri, Komang Ayu; Sujaya, I Nengah; Ramona, Yan (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 6 No 1 (2019): Scientific Journal of Food Technology (March), 2020)
Lactobacillus rhamnosus FBB81 is a probiotic candidate isolated from healthy infant feces that has functional properties as an antioxidant. Probiotics are made in the form of a dry cell by microencapsulation technique to facilitate the application of probiotics in the development of functional food products. The purpose of this study was to determine the viability of Lb. rhamnosus FBB81 encapsulated with maltodextrin and skim milk during storage. The microencapsulated product was stored at two storage temperatures namely room temperature and cold temperature. The viability of Lb. rhamnosus FBB81 on the microencapsulated product was observed every 1 week for 8 weeks of storage. The results showed that the types of encapsulan and storage temperature affected the viability of Lb. rhamnosus FBB81 during storage. Skim milk and cold temperatures have a better ability than the maltodextrin and room temperature in maintaining the viability of probiotic Lb. rhamnosus FBB81 during storage.